Clinical Sports Medicine - Liebich C; Wergin VV; Schubert I; Von Bruehl ML; Marquart C; Halle M; 4; Oberhoffer R; Wolfarth B (Dynamic Media Sales Verlag, 2021)
Problem: The skin is exposed to numerous stresses during sport. In addition to infection-related or allergic triggers, the development of sport-associated skin diseases depends on the discipline practiced and can be caused by mechanical stressors, thermal damage, and UV radiation. Methods: This review intends to give an overview of study results on the incidence and prevalence of skin diseases in competitive athletes. Publications describing case reports of the outbreak of a specific skin disease within a small cohort of athletes of a defined discipline were included as well as publications comparing the incidence of dermatoses between different disciplines based on large study cohorts.Results: Most studies focus on the analysis of the ocurrence of certain skin diseases in athletes of only one defined discipline, in most cases athletes performing sports with close body contact. Hardly any studies deal with dermatoses in competitive athletes among multiple disciplines. This review displays the occurrence of infectious, allergic, traumatic, UV-induced, and sebaceous dermatoses in competitive athletes by taking different disciplines into account.Discussion: Depending on the training environment, flow of movement, climatic influences and other factors, certain skin diseases occur frequently in athletes of specific disciplines.Key Words: High-Performance Athlete, Skin Disease, Training, Specific Disciplines